2011
DOI: 10.1152/ajpcell.00514.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells function as an alternative modulator of adipogenesis through 15-deoxy-delta-12, 14-prostaglandin J2

Abstract: Mast cells are one of the major producers of prostaglandins (PGs). The final metabolite of PGs 15-deoxy-delta-12,14-PGJ2(15-deoxy-delta PGJ2) is the endogenous ligand of the peroxisome proliferator-activated receptor (PPAR) γ. PPARγ modulates adipocyte differentiation; therefore, we attempted to investigate whether PGs derived from mast cells influenced on adipogenesis. We found the increase of mast cell numbers in fat tissue of obese mice fed with a high-fat diet allowed us to speculate contributions of mast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 48 publications
4
53
0
1
Order By: Relevance
“…In addition, the obesity-related increase of mast cell numbers is more prominent in gAT (29), thereby suggesting that mast cells might participate in obesity-related AT inflammation and metabolic dysregulation (12). The proposed effects of mast cells in obesity, however, were inferred from experiments in Kit mutant mast cell-deficient mouse strains Kit W/W-v and Kit W-sh/W-sh (12, 13, 18), which displayed significantly lower weight gain and an improved obesity-related metabolic and inflammatory phenotype as compared to control mice. This effect was attributed to the lack of mast cell-derived IFN-γ and IL-6 (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the obesity-related increase of mast cell numbers is more prominent in gAT (29), thereby suggesting that mast cells might participate in obesity-related AT inflammation and metabolic dysregulation (12). The proposed effects of mast cells in obesity, however, were inferred from experiments in Kit mutant mast cell-deficient mouse strains Kit W/W-v and Kit W-sh/W-sh (12, 13, 18), which displayed significantly lower weight gain and an improved obesity-related metabolic and inflammatory phenotype as compared to control mice. This effect was attributed to the lack of mast cell-derived IFN-γ and IL-6 (12).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that MC supernatant contains 15-deoxy-delta PGJ 2 that induces pre-adipocyte 3T3-L1 cell adipogenesis (Figure 2). The specific PPARγ antagonist GW9662 blocks this MC activity (Tanaka et al, 2011). Using MC-deficient Kit W/Wv mice, the investigators showed that reduced body weight in Kit W/Wv mice can be reversed by WT bone marrow-derived mast cell (BMMC) transplantation, but not by transplantation of BMMC from hematopoietic PGD synthase (H-PGDS)-deficient mice.…”
Section: Mast Cells In Obesitymentioning
confidence: 99%
“…Using MC-deficient Kit W/Wv mice, the investigators showed that reduced body weight in Kit W/Wv mice can be reversed by WT bone marrow-derived mast cell (BMMC) transplantation, but not by transplantation of BMMC from hematopoietic PGD synthase (H-PGDS)-deficient mice. H-PGDS-deficient BMMC also failed to induce 3T3-L1 differentiation (Tanaka et al, 2011). …”
Section: Mast Cells In Obesitymentioning
confidence: 99%
“…Likewise, mast cells are shown to co-localize with CD8 þ T cells in mouse WAT (Xu and Shi, 2012) suggesting a role in adipose tissue inflammation. An additional study reported that mast cell deficient Kit W-sh/W-sh mice transplanted with hematopoietic-prostaglandin synthase deficient mast cells are not able to gain weight similarly as mice transplanted with wild-type mast cells, pinpointing the importance of mast cell derived prostaglandins in adipose tissue function (Tanaka et al, 2011). As adipocytes themselves are also an important source of cytokines (Cao, 2014), this adds up to the local inflammatory burden.…”
Section: Diet-induced Obesitymentioning
confidence: 99%